2012
DOI: 10.1155/2012/134723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Mineral Elements Supplementation in the Treatment of Hypertension in Albino Rats

Abstract: Oxidative stress has been implicated in various pathologies, including hypertension, atherosclerosis, diabetes, and chronic renal disease. The current work was designed with the aim of investigating the potentials of antioxidants copper, manganese, and zinc in the treatment of hypertension in Wistar rats. The rats were fed 8% NaCl diet for 5 weeks and treatment with supplements in the presence of the challenging agent for additional 4 weeks. The supplementation significantly decreased the blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In our experiment, the increase in plasma TAG concentration could have resulted from a higher Cu:Zn ratio in blood plasma. Hypercholesterolemia induced by Zn deficiency due to higher dietary intake of Cu was reported in a study of rats (Muhammad et al 2012). In our experiment, plasma TP concentration increased with a rise in the dietary inclusion levels of Cu.…”
Section: Discussionsupporting
confidence: 76%
“…In our experiment, the increase in plasma TAG concentration could have resulted from a higher Cu:Zn ratio in blood plasma. Hypercholesterolemia induced by Zn deficiency due to higher dietary intake of Cu was reported in a study of rats (Muhammad et al 2012). In our experiment, plasma TP concentration increased with a rise in the dietary inclusion levels of Cu.…”
Section: Discussionsupporting
confidence: 76%
“…Our results are in conformity with the finding of Jing et al (2007), who fed rats on different Zn levels for 6 weeks and reported that rats fed on Zn deficient diet had reduced activities of copper-zinc superoxide dismutase (Cu-Zn SOD) and CAT; and increased malondialdehyde as well as hydrogen peroxide concentrations in liver. Similarly, Muhammad (2012) found that supplementation of antioxidant minerals to the albino rats increased the activities of CAT, Gpx, and SOD as compared with hypertensive control. Nevertheless, CAT activity in the present study was comparable among treatment groups.…”
Section: Resultsmentioning
confidence: 85%
“…Similar to our study, Atakisi et al 24 observed that treatment with zinc on quills raised the NO level in the body. Muhammad et al 41 also showed that the administration of zinc improved endothelial function by increasing the NO level when compared with hypertensive control rats. In our study, zinc is decreasing the oxidative stress by attenuating lipid peroxidation and increasing the non-enzymatic antioxidant.…”
Section: Effect On Liver Functionmentioning
confidence: 96%